Na 4-x Fe3(PO4) 2-x (SO4) x P2O7 / C material and its preparation method and application
By preparing Na4-xFe3(PO4)2-x(SO4)xP2O7/C material, the problem of low average charge and discharge voltage of the existing sodium ion battery positive electrode material is solved, and high energy density and good stability are achieved.
Patent Information
- Application Number
- CN202311718570.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-14
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-12-14
AI Technical Summary
The average charge and discharge voltage of the positive electrode materials of existing sodium ion batteries is low, resulting in low energy density, which limits the practical value of the material.
Using Na4-xFe3(PO4)2-x(SO4)xP2O7/C material, mix sodium carbonate, ammonium dihydrate, ferrous sulfate heptahydrate, ferrous oxalate dihydrate, carbon source and water, and then grind it inert Sintered in an atmosphere to prepare a composite material with a high average charge and discharge voltage.
The discharge specific capacity at 1C ratio reached 96.3mAh·g-1, and the charge and discharge efficiency of 100 cycles was maintained at about 99.8%, showing good stability and high energy density.
Smart Images

Figure CN117776136B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of materials, and in particular to a Na 4-x Fe3(PO4) 2-x (SO4) x P2O7 / C material, preparation method and application thereof. Background Art
[0002] There are a large number of reports on positive electrode materials for sodium-ion batteries in the existing technology, but the electrochemical properties of most materials are poor, such as vanadium-based phosphates, iron-based phosphates or Prussian blue analogs. Moreover, in the process of commercial transformation of laboratory results, these materials face some serious problems, such as the high toxicity and high cost of vanadium-based materials, and the structural instability of Prussian blue analogs. Conventional sodium iron pyrophosphate has the problem of low charging and discharging platform, resulting in low overall energy density and shortcomings in practical applications. Although there are many improvement schemes for sodium iron pyrophosphate in the existing technology, there is still a lot of room for exploration and improvement.
[0003] How to improve the average charge and discharge voltage of materials, increase the energy density of materials, and further expand the practical value of materials are issues that existing technologies need to develop and consider. Summary of the invention
[0004] The object of the present invention is to overcome the above-mentioned technical deficiencies and provide a Na 4-x Fe3(PO4) 2-x (SO4) x The P2O7 / C material and its preparation method and application solve the technical problem of low average charge and discharge voltage of the material in the prior art.
[0005] In order to achieve the above technical purpose, the technical solution of the present invention provides a Na 4-x Fe3(PO4) 2-x (SO4) x The preparation method of P2O7 / C material comprises the following steps:
[0006] S1. mixing sodium carbonate, ammonium dihydrogen phosphate, ferrous sulfate heptahydrate, ferrous oxalate dihydrate, a carbon source and water to obtain a mixture;
[0007] S2, grinding the mixture to obtain a slurry, and drying the slurry to obtain a precursor;
[0008] S3, sintering the precursor in an inert atmosphere at a temperature of 550-800° C. to obtain the Na 4-x Fe3(PO4) 2-x (SO4) xP2O7 / C composite material, 0<x≤1.
[0009] Further, in certain embodiments, in step S1, the molar ratio of the sodium carbonate to the diammonium phosphate is 1:(2-3); the molar ratio of the ferrous sulfate heptahydrate to the ferrous oxalate dihydrate is 1:(2-3); the molar ratio of the diammonium phosphate to the ferrous oxalate dihydrate is (3-4.5):(2-3).
[0010] Further, in certain embodiments, in step S1, the molar ratio of the carbon source to the ferrous sulfate heptahydrate is (0.5-1):1; the usage ratio of the ferrous sulfate heptahydrate to the water is 3 mol:(5-18) L; and / or, in step S1, the carbon source is glucose.
[0011] Furthermore, in some embodiments, in step S2, the particle size of the slurry is D50≤0.4 μm and D100≤1.2 μm.
[0012] Further, in certain embodiments, in step S2, the mixture is ground in a grinder at a speed of 1000-3500 rpm for 0.5-3 h to obtain a slurry.
[0013] Further, in certain embodiments, in step S2, the slurry is sent to a spray dryer for drying, with an air inlet temperature of 210-230°C, an air outlet temperature of 120-140°C, and a spray rate of 5-12 L / h.
[0014] Further, in some embodiments, in step S3, the temperature is increased to 550-800°C at a heating rate of 2.5-3°C / min.
[0015] Further, in some embodiments, in step S3, the sintering time at 550-800° C. is 5-6 h.
[0016] In addition, the present invention also proposes a Na 4-x Fe3(PO4) 2-x (SO4) x The P2O7 / C material is prepared by the above preparation method.
[0017] In addition, the present invention also proposes Na obtained by the above preparation method 4-x Fe3(PO4) 2-x (SO4) x P2O7 / C material or the above Na 4-x Fe3(PO4) 2-x (SO4) x Application of P2O7 / C material as positive electrode material in batteries.
[0018] Compared with the prior art, the beneficial effects of the present invention include: the present invention provides a Na 4-x Fe3(PO4) 2-x (SO4) x The preparation method of P2O7 / C material comprises the following steps: using sodium carbonate, ammonium dihydrogen phosphate, ferrous sulfate heptahydrate, ferrous oxalate dihydrate, a carbon source and water as raw materials, first mixing and then grinding, and then sintering in an inert atmosphere at a temperature of 550-800°C to obtain the Na 4-x Fe3(PO4) 2-x (SO4) x The P2O7 / C material has a high average charge and discharge voltage. At a rate of 1C, the discharge capacity reaches 96.3 mAh g -1 At the same time, the charge and discharge efficiency of 100 cycles at 1C rate remained at around 99.8%, showing good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is Na obtained in Example 1 of the present invention. 4-x Fe3(PO4) 2-x (SO4) x Scanning electron microscope image of P2O7 / C composite material.
[0020] Figure 2 It is Na obtained in Example 1 of the present invention. 4-x Fe3(PO4) 2-x (SO4) x XRD pattern of P2O7 / C composite material.
[0021] Figure 3 It is a charge and discharge curve diagram of the positive electrode materials prepared in Example 1 of the present invention and Comparative Example 1.
[0022] Figure 4 It is a charge and discharge cycle diagram of the positive electrode materials prepared in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0023] This specific embodiment provides a Na 4-x Fe3(PO4) 2-x (SO4) x The preparation method of the P2O7 / C composite material comprises the following steps:
[0024] S1. Mix sodium carbonate, ammonium dihydrogen phosphate, ferrous sulfate heptahydrate, ferrous oxalate dihydrate, a carbon source and water to obtain a mixture; the molar ratio of the sodium carbonate to the ammonium dihydrogen phosphate is 1:(2-3); the molar ratio of the ferrous sulfate heptahydrate to the ferrous oxalate dihydrate is 1:(2-3); the molar ratio of the ammonium dihydrogen phosphate to the ferrous sulfate heptahydrate is (3-4.5):(2-3); the molar ratio of the carbon source to the ferrous sulfate heptahydrate is (0.5-1):1; the carbon source is glucose; the dosage ratio of the ferrous sulfate heptahydrate to the water is 3 mol:(5-18) L;
[0025] S2, grinding the mixture to obtain a slurry, further grinding the mixture in a grinder at a speed of 1000-3500 rpm for 0.5-3 h to obtain a slurry, drying the slurry to obtain a precursor, further sending the slurry to a spray dryer for drying, with an inlet air temperature of 210-230° C., an outlet air temperature of 120-140° C., and a spray rate of 5-12 L / h; the particle size of the slurry is D50≤0.4 μm, and D100≤1.2 μm;
[0026] S3, sintering the precursor in an inert atmosphere at a temperature of 550-800° C. for 5-6 hours to obtain the Na 4- x Fe3(PO4) 2-x (SO4) x The P2O7 / C composite material is further heated to 550-800°C at a heating rate of 2.5-3°C / min.
[0027] This specific implementation method also proposes a Na 4-x Fe3(PO4) 2-x (SO4) x The P2O7 / C composite material is prepared by the above preparation method.
[0028] In addition, this specific embodiment also proposes Na obtained by the above preparation method 4-x Fe3(PO4) 2-x (SO4) x P2O7 / C composite material or the above Na 4-x Fe3(PO4) 2-x (SO4) x Application of P2O7 / C composite materials as positive electrode materials in batteries.
[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0030] Example 1
[0031] This embodiment proposes a Na 4-x Fe3(PO4) 2-x (SO4) x The P2O7 / C composite material is prepared by the following steps:
[0032] S1. Add 10L of deionized water as a solvent into a stirring tank, weigh 4.5mol of sodium carbonate (Na2CO3), 9mol of ammonium dihydrogen phosphate (NH4H2PO4), 3mol of ferrous sulfate heptahydrate (FeSO4·7H2O) and 6mol of ferrous oxalate dihydrate (FeC2O4·2H2O) as raw materials; at the same time, add 1.5mol of glucose as a carbon source, add the raw material powder and glucose into a stirring bar, set the stirring speed to 400rmp; mix for 30min, and stir to obtain a mixture;
[0033] S2. The mixture is transferred to a sand mill, the speed of the sand mill is set to 2000 rpm, the sand milling time is 2 h, and the particle size of the slurry is controlled at D50 ≤ 0.4 μm and D100 ≤ 1.2 μm; the ground slurry is transferred to a spray dryer, the inlet air temperature is set to 230 ° C, the outlet air temperature is controlled at about 130 ° C, and the spray rate is set to 10 L / h. After the spraying is completed, the precursor powder is obtained;
[0034] S3, the precursor powder obtained in step S2 was transferred to a box-type atmosphere furnace, and an inert atmosphere of argon was introduced for sintering. The heating rate was set to 2.5°C / min and the temperature was raised to 650°C. The temperature was kept for 5 hours. After the furnace temperature was cooled, Na 4-x Fe3(PO4) 2-x (SO4) x P2O7 / C composite material.
[0035] Combination Figure 1 It can be seen that the morphology of the prepared composite material is spherical particles with smooth surface. Figure 2 It can be seen from the XRD pattern that the preparation method proposed in the present invention successfully prepared Na 4-x Fe3(PO4) 2-x (SO4) x P2O7 / C composite material.
[0036] Example 2
[0037] This embodiment proposes a Na 4-x Fe3(PO4) 2-x (SO4) x The P2O7 / C composite material is prepared by the following steps:
[0038] S1. Add 5L of deionized water as a solvent into a stirring tank, weigh 4.5mol of sodium carbonate (Na2CO3), 12mol of ammonium dihydrogen phosphate (NH4H2PO4), 3mol of ferrous sulfate heptahydrate (FeSO4·7H2O) and 9mol of ferrous oxalate dihydrate (FeC2O4·2H2O) as raw materials; at the same time, add 2mol of glucose as a carbon source, add the raw material powder and glucose into a stirring bar, set the stirrer speed to 400rmp; mix for 30min, and stir evenly to obtain a mixture;
[0039] S2. The mixture is transferred to a sand mill, the speed of the sand mill is set to 3500rmp, the sand milling time is 0.5h, and the particle size of the slurry is controlled at D50≤0.4μm and D100≤1.2μm; the ground slurry is transferred to a spray dryer, the inlet air temperature is set to 210°C, the outlet air temperature is controlled at about 120°C, the spray rate is set to 5L / h, and the precursor powder is obtained after the spraying is completed;
[0040] S3, the precursor powder obtained in step S2 was transferred to a box-type atmosphere furnace, and an inert atmosphere of argon was introduced for sintering. The heating rate was set to 3°C / min and the temperature was raised to 550°C, and the temperature was kept for 6 hours. After the furnace temperature was cooled, Na 4-x Fe3(PO4) 2-x (SO4) x P2O7 / C composite material.
[0041] Example 3
[0042] This embodiment proposes a Na 4-x Fe3(PO4) 2-x (SO4) x The P2O7 / C composite material is prepared by the following steps:
[0043] S1. Add 18L of deionized water as a solvent into a stirring tank, weigh 4.5mol of sodium carbonate (Na2CO3), 13.5mol of ammonium dihydrogen phosphate (NH4H2PO4), 3mol of ferrous sulfate heptahydrate (FeSO4·7H2O) and 8mol of ferrous oxalate dihydrate (FeC2O4·2H2O) as raw materials; at the same time, add 3mol of glucose as a carbon source, add the raw material powder and glucose to a stirring bar, set the stirrer speed to 400rmp; mix for 30min, and stir evenly to obtain a mixture;
[0044] S2. The mixture was transferred to a sand mill, the sand mill speed was set to 1000 rpm, the sand milling time was 3 h, and the particle size of the slurry was controlled at D50 ≤ 0.4 μm and D100 ≤ 1.2 μm; the ground slurry was transferred to a spray dryer, the inlet air temperature was set to 220 ° C, the outlet air temperature was controlled at about 140 ° C, the spray rate was set to 12 L / h, and the precursor powder was obtained after the spraying was completed;
[0045] S3, the precursor powder obtained in step S2 was transferred to a box-type atmosphere furnace, and an inert atmosphere of argon was introduced for sintering. The heating rate was set to 2.5°C / min and the temperature was raised to 800°C, and the temperature was kept for 5 hours. After the furnace temperature was cooled, Na 4-x Fe3(PO4) 2-x (SO4) x P2O7 / C composite material.
[0046] Comparative Example 1
[0047] This comparative example proposes a method for preparing a composite material. The main difference between this method and Example 1 is that ferrous sulfate heptahydrate is not added, but sodium pyrophosphate is added, as follows:
[0048] S1. Add 10L of deionized water as a solvent into a stirring tank, weigh 3 mol of sodium pyrophosphate (Na4P2O7), 6 mol of diammonium phosphate (NH4H2PO4) and 9 mol of ferrous oxalate dihydrate (FeC2O4·2H2O) as raw materials; add 1.5 mol of glucose as a carbon source, slowly add all the raw material powders and glucose into the stirring tank, set the stirrer speed to 400 rpm; mix for 30 min, and mix evenly to obtain a mixture;
[0049] S2. The mixture is transferred to a sand mill, the speed of the sand mill is set to 2000 rpm, the sand milling time is 2 h, and the particle size of the slurry is controlled at D50 ≤ 0.4 μm and D100 ≤ 1.2 μm; the ground slurry is transferred to a spray dryer, the inlet air temperature is set to 230 ° C, the outlet air temperature is controlled at about 130 ° C, and the spray rate is set to 10 L / h. After the spraying is completed, the precursor powder is obtained;
[0050] S3. Transfer the precursor powder in step S2 to a box-type atmosphere furnace, introduce an inert atmosphere for sintering, set the sintering temperature to 650°C, keep warm for 5 hours, and increase the temperature at a rate of 2.5°C / min. After the furnace temperature is cooled, a Na4Fe3(PO4)2P2O7 / C composite material is obtained.
[0051] According to the following button cell preparation method, the Na prepared in Example 1 was used. 4-x Fe3(PO4) 2-x (SO4)x Button cells were prepared using the P2O7 / C composite material and the Na4Fe3(PO4)2P2O7 / C composite material prepared in Comparative Example 1 as positive electrode materials.
[0052] The preparation method of button cell is as follows:
[0053] The prepared composite material was weighed as the positive electrode material, acetylene black was added as the conductive agent, and PVDF was added as the binder. After sufficient grinding, a mixed slurry was obtained, and an appropriate amount of N-methylpyrrolidone (NMP) was added to form a uniform black paste slurry (wherein the composite material was 80% of the mass of the mixture, acetylene black was 10% of the mass of the mixture, and PVDF was 10% of the mass of the mixture). The obtained slurry was coated on an aluminum foil sheet, placed in a vacuum oven at 120°C and dried for 8 hours, and then cut into circular pole pieces with a diameter of 14 mm using a cutting machine, and the pole pieces were made into CR2025 button batteries in a high-purity argon glove box. At room temperature (25°C), the constant current charge and discharge test was carried out with a limiting voltage of 1.7 to 4.3V. The electrolyte system used was 1M NaPF6 / EC:DMC (1:1) + 5% FEC.
[0054] like Figure 3 and 4 As shown in Figure 1, the composite material prepared in Example 1 has a discharge capacity of up to 96.3 mAh·g at a rate of 1C. -1 At the same time, the charge and discharge efficiency of 100 cycles at a rate of 1C remained at about 99.8%, showing good stability; while the composite material of comparative example 1 had a discharge capacity of only 80.1 mAh g at a rate of 1C. -1 At the same time, the charge and discharge efficiency after 100 cycles at a 1C rate is only about 85.5%, and the stability is poor.
[0055] This may be because sulfate has a stronger electronegativity than phosphate, which makes the positive electrode material of the sodium ion battery have a higher voltage platform. Combined with other processes and raw materials, the charge and discharge efficiency of the composite material is higher.
[0056] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A Na 4-x Fe3(PO4) 2-x (SO4) x The preparation method of P2O7 / C material is characterized in that: The following steps are involved: S1. Mix sodium carbonate, ammonium dihydrogen phosphate, ferrous sulfate heptahydrate, ferrous oxalate dihydrate, a carbon source and water to obtain a mixture; the molar ratio of the sodium carbonate to the ammonium dihydrogen phosphate is 1:(2-3); the molar ratio of the ferrous sulfate heptahydrate to the ferrous oxalate dihydrate is 1:(2-3); the molar ratio of the ammonium dihydrogen phosphate to the ferrous oxalate dihydrate is (3-4.5):(2-3); the molar ratio of the carbon source to the ferrous sulfate heptahydrate is (0.5-1):1; the dosage ratio of the ferrous sulfate heptahydrate to the water is 3 mol:(5-18) L; the carbon source is glucose; S2, grinding the mixture to obtain a slurry, and drying the slurry to obtain a precursor; S3, placing the precursor in an inert atmosphere at room temperature in a box-type atmosphere furnace, raising the temperature to 550-800°C at a heating rate of 2.5-3°C / min, and sintering for 5-6h to obtain the Na 4-x Fe3(PO4) 2-x (SO4) x P2O7 / C composite material, 0<x≤1.
2. Na according to claim 1 4-x Fe3(PO4) 2-x (SO4) x The preparation method of P2O7 / C material, in step S2, the particle size of the slurry is D50≤0.4μm, D100≤1.2μm.
3. Na according to claim 1 4-x Fe3(PO4) 2-x (SO4) x The preparation method of P2O7 / C material comprises the following steps: in step S2, grinding the mixture in a grinder at a speed of 1000-3500 rpm for 0.5-3 h to obtain the slurry.
4. Na according to claim 1 4-x Fe3(PO4) 2-x (SO4) x The preparation method of P2O7 / C material comprises the following steps: in step S2, the slurry is sent to a spray dryer for drying, the inlet air temperature is 210-230°C, the outlet air temperature is 120-140°C, and the spray rate is 5-12L / h.
5. A Na 4-x Fe3(PO4) 2-x (SO4) x P2O7 / C material, characterized in that The invention is prepared by the preparation method according to any one of claims 1 to 4.
6. Na obtained by the preparation method according to any one of claims 1 to 4 4-x Fe3(PO4) 2-x (SO4) x P2O7 / C material or Na2O7 / C material according to claim 5 4-x Fe3(PO4) 2-x (SO4) x Application of P2O7 / C material as positive electrode material in batteries.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery
CN115050957A
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN116534830A